2020
DOI: 10.15585/mmwr.rr6908a1
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and Control of Seasonal Influenza with Vaccines: Recommendations of the Advisory Committee on Immunization Practices — United States, 2020–21 Influenza Season

Abstract: Recommendations for routine use of vaccines in children, adolescents, and adults are developed by the Advisory Committee on Immunization Practices (ACIP). ACIP is chartered as a Federal Advisory Committee to provide expert external advice and guidance to the Director of CDC on use of vaccines and related agents for the control of vaccine preventable diseases in the civilian population of the United States. Recommendation for routine use of vaccines in children and adolescents are harmonized to the greatest ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
251
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 299 publications
(262 citation statements)
references
References 83 publications
2
251
0
4
Order By: Relevance
“…Although the main information provided corresponded to the benefits of the vaccine, a fact recognized worldwide [ 26 ], in 41.0% of the videos, a positive tone was not found, which indicates that the information in YouTube videos regarding the flu vaccine is often incomplete. This deficiency of information in YouTube videos that focus on the influenza vaccine can be confirmed by observing the low frequency of certain recommendations of the World Health Organization (WHO) [ 27 ] adopted in Spain [ 28 ], the USA [ 29 ], and Hispanic American countries [ 30 , 31 ], such as recommendations to vaccinate healthcare workers annually to reduce the risk of acquiring the influenza and transmitting it to their patients [ 28 , 29 , 32 ]. Similarly, other WHO recommendations adopted in such countries [ 27 , 28 , 29 , 30 , 31 ], such as vaccinating people over 65 years of age, did not appear in half of the videos, even if the recommendation is described as such, or in the context of expanding vaccination in certain countries by including a recommendation to vaccinate people over 60 years of age [ 30 , 31 ] or the entire population over 6 months of age [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the main information provided corresponded to the benefits of the vaccine, a fact recognized worldwide [ 26 ], in 41.0% of the videos, a positive tone was not found, which indicates that the information in YouTube videos regarding the flu vaccine is often incomplete. This deficiency of information in YouTube videos that focus on the influenza vaccine can be confirmed by observing the low frequency of certain recommendations of the World Health Organization (WHO) [ 27 ] adopted in Spain [ 28 ], the USA [ 29 ], and Hispanic American countries [ 30 , 31 ], such as recommendations to vaccinate healthcare workers annually to reduce the risk of acquiring the influenza and transmitting it to their patients [ 28 , 29 , 32 ]. Similarly, other WHO recommendations adopted in such countries [ 27 , 28 , 29 , 30 , 31 ], such as vaccinating people over 65 years of age, did not appear in half of the videos, even if the recommendation is described as such, or in the context of expanding vaccination in certain countries by including a recommendation to vaccinate people over 60 years of age [ 30 , 31 ] or the entire population over 6 months of age [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review by Demicheli et al found that the incidence of influenza infection was reduced by approximately 60% in healthy people who were vaccinated against influenza virus 10 . Due to comorbidities, such as malignancy, or medications, including chemotherapy, immunocompromised persons are at relatively higher risk for experiencing medical complications from severe influenza 16 . Therefore, guidelines recommend that immunocompromised persons be vaccinated against influenza 16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…Due to comorbidities, such as malignancy, or medications, including chemotherapy, immunocompromised persons are at relatively higher risk for experiencing medical complications from severe influenza 16 . Therefore, guidelines recommend that immunocompromised persons be vaccinated against influenza 16,17 . Although these guidelines strongly recommend influenza vaccination for such patients, the supporting evidence for this recommendation is somewhat weak.…”
Section: Discussionmentioning
confidence: 99%
“…During the 2020 to 2021 influenza season, it is anticipated that HD-IIV4 will replace HD-IIV3. 11 , 16 Both aIIV4 and aIIV3 products are expected to be distributed during the 2020 to 2021 influenza season. 11 In addition to these age-specific vaccines, quadrivalent standard-dose, unadjuvanted inactivated influenza vaccines (SD-IIV4) and quadrivalent recombinant influenza vaccine (RIV4) are licensed and recommended for people aged 65 years and older.…”
Section: Introductionmentioning
confidence: 99%